2020
DOI: 10.3126/jsp.v1i0.38209
|View full text |Cite
|
Sign up to set email alerts
|

Social Protection in Health: Characteristics and Coverage of Health Insurance Programme in Nepal

Abstract: The agenda of social protection has become very popular in recent years. Several social protection programs in healthcare are designed to increase the healthcare coverage, ensure financial protection and enhance the scope and quality of services and access to medicines which ultimately paves the way for universal health coverage. The national health insurance programme (NHIP) is one of the approaches implemented in Nepal to cover healthcare expenditure. This paper discusses the gradual development of the healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Nepal faces the challenge of extending social security benefits to all workers operating in the informal economy, which accounts for more than 90 per cent of the total labour force (Khanal, 2013). Social assistance programs are marred by various problems (Kohler, 2014).…”
Section: Practices Of Policy Response To Social Protection In Nepalmentioning
confidence: 99%
See 2 more Smart Citations
“…Nepal faces the challenge of extending social security benefits to all workers operating in the informal economy, which accounts for more than 90 per cent of the total labour force (Khanal, 2013). Social assistance programs are marred by various problems (Kohler, 2014).…”
Section: Practices Of Policy Response To Social Protection In Nepalmentioning
confidence: 99%
“…All tiers of government must offer social protection services, including social allowances, to citizens identified as poor, as per the constitutional mandate. The federal government's current social insurance scheme excludes over 90 percent of workers, i.e., those in the informal sector, who often work in the most precarious conditions (Khanal, D. R. (2013). These workers are disproportionately women and from marginalized ethnic groups.…”
Section: Practices Of Policy Response To Social Protection In Nepalmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of Lindner's (1998) study of 25 employees at the Piketon Research and Extension Centre and Enterprise Centre found that good working conditions ranked fifth among top ten factors that motivated employees at work. Apart from improving working conditions, the provision of overall social security benefits such as family benefits, unemployment benefits, medical insurance, and maternity benefits, among others, to workers are also important and their presence contribute to raising labour productivity and curbing social tensions, violent conflicts, and uncontrolled migration (Khanal, 2012). Government, as a key industrial relations actor, can provide a regulatory environment through its laws and policies that can improve working conditions and increase employees' welfare.…”
Section: Government and Employees' Welfarementioning
confidence: 99%
“…The workers' situation in various industries including tourism is particularly challenging as a large number of workers, as much as 90 per cent of the total workforce, operate in informal sectors such as farms, trading, crafts business, and transportation among others (Khanal, 2012). Although the government of Nepal has expressed its commitment to expand safety nets and social protection coverage for these workers through the new Labour Act 2017, they have typically been deprived of social protection benefits such as universal family benefits, social assistance, and social insurance.…”
Section: Employment Policies and Practices In Nepalmentioning
confidence: 99%